Estrutura de pastagem natural e desempenho de vacas e novilhas em pastoreio rotativo - Marin, Luciana (2019)
The beef cattle production in Rio Grande do Sul is based mainly on extensive breeding systems where animal feed basis are natural grasslands. The present work aimed to evaluate the forage production and the productive performance of heifers and cows managed in natural grassland under the “first” and “last” grazers rotational grazing system. The treatments were two rest intervals between grazing, from 402 degree-day and 252 degree-days, which prioritized the growth of grasses of conservation and resource use groups, respectively. Twenty-four tester heifers were used to constitute the “first” group and 24 tester cows constituting the "last"group. The sward structure descriptors did not show treatment x period interaction , the mean height were higher in the 402 GD treatment , total forage mass, forage mass of lower stratum, density and % of structural components were similar between treatments. The animal stocking was adjusted with regulatory heifers in the "first" group for the intake of 70% of leaf blades in a forage mass above 1000 kg MS.ha-1. The daily weight gain (DWG) of heifers was similar between rest intervals (P> 0.05) with a mean of 0.222 kg.day-1. Cow DWG was also similar between treatments (P> 0.05), with an average of 0.320 kg. day-1. The body weight gain per hectare was higher in the treatment of less rest interval, where during the 149 days of experiment there was a gain of 117 kg. ha-1, whereas in the treatment of a longer interval the gain was 95 kg. ha-1. The rotational grazing system with "first" and "last" grazers provided satisfactory performances, proving to be a useful tool in the rearing of heifers for mating at 24 months and termination of cull cows.